ON THE PROSPECTS FOR SHAPING A CIVIL NATION IN DAGHESTAN - BILALOV, Mustafa (CENTRAL ASIA AND THE CAUCASUS, 2012)
Russia’s integrity depends on ensuring civil identity as a priority factor in the development of society and the individual. Civil identity is fully realized in a civil nation that gradually takes shape within a particular society. The crisis of multiculturalism in the West triggered by the crisis of the European civilization and culture calls for a revision of certain ideas and theories associated with civil identity. The question is whether the national regions of Russia (including Daghestan) will manage to adjust themselves to Western civilization in the specific conditions of a multinational and multi-confessional society. This article is intended as an assessment of the general prospects for shaping a civil nation in Daghestan.